Analisis Balanced Scorecard Sebagai Alat Pengukur Kinerja - Febrian Aji Prakoso; Tabrani (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2017)
The purpose of the research is to analyze the performance of KUD Karya Mina Tegal with Balanced Scorecard. Data collection method used in this research is questionnaire. Performance of KUD Karya Mina Tegal is viewed from a financial perspective using Profitability ratio instrument consisting of current ratio, return on investment, and net profit margin. Of the three instruments, only the current ratio is in accordance with the standard, while return on investment and net profit margin is still below the specified standard. Performance of KUD Karya Mina Tegal from customer perspective with member satisfaction indicator and member acquisition in good category. This can be seen from the increasing trend seen from the increase in the number of members each year as well as from the increased percentage increase in member acquisition. The performance of KUD Karya Mina Tegal is viewed from the internal perspective of the business with indicators of innovation and operation is considered good. Viewed from how KUD Karya mina is able to see the needs of its members and provide additional benefits to the members. The performance of KUD Karya Mina from learning and growth perspective with employee satisfaction indicator, employee retention and employee training is considered good. In the indicator of employee satisfaction, employees feel satisfied in working in KUD Karya Mina Tegal. For employee retention from year to year decreased, this can be interpreted that KUD Karya Mina Tegal able to retain its employees. And for employee training seen from the increasing trend every year. The results of the overall performance measurement of KUD Karya Mina Tegal is in good area, with a total score of 86,66% . That is, the performance of KUD Karya Mina Tegal good if measured by Balanced Scorecard approach.